On Bitcoin: A Study in Applied Metaphysics. - Lipman, Martin A (Philosophical Quarterly, 2023)
This essay is dedicated to the memory of Katherine Hawley. Bitcoin was invented to serve as a digital currency that demands no trust in financial institutions, such as commercial and central banks. This paper discusses metaphysical aspects of bitcoin, in particular the view that bitcoin is socially constructed, non-concrete, and genuinely exists. If bitcoin is socially constructed, then one may worry that this reintroduces trust in the communities responsible for the social construction. Although we may have to rely on certain communities, I argue that social construction doesn't imply a demand for trust because the relevant communities don't take on any relevant commitments. Bitcoin is indeed trust-free.